Supported catalyst as well as preparation method and application thereof

By acid treatment and molding, and loading palladium and additives onto the support, a supported catalyst with high selectivity and long life is prepared, which solves the problems of low catalyst selectivity and short service life in the prior art, and reduces production costs.

CN119819322APending Publication Date: 2025-04-15WANHUA CHEM GRP CO LTD

Patent Information

Application Number
CN202510001237.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In the oxidation reaction of ethylene and propylene, the supported catalyst has low selectivity and short service life, resulting in high production costs of vinyl acetate and allyl acetate.

Method used

The natural calcium-based bentonite is treated by acid to obtain modified bentonite, and manganese oxide and copper oxide powder are added during the molding process to prepare a carrier. Then, palladium and additives are loaded onto the support by deposition precipitation method, and a supported catalyst with high selectivity and long life is prepared.

Benefits of technology

It improves the selectivity and service life of the catalyst, reduces the production costs of vinyl acetate and allyl acetate, and provides a competitive catalyst process route.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005225237240000061
    Figure BDA0005225237240000061
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a carrier molding and supported catalyst. The preparation method comprises the following steps: selecting proper natural calcium bentonite, carrying out acid treatment modification on the natural calcium bentonite, washing, drying and crushing to obtain modified bentonite powder with high purity and proper particle size distribution; adding manganese oxide and copper oxide into the powder, carrying out compression molding together with a binder, and roasting to obtain the carrier. The catalyst prepared by loading the active component on the surface of the carrier can be used in the oxyacylation reaction of ethylene and propylene, and has excellent selectivity and long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a supported catalyst and a preparation method thereof, and application of the supported catalyst in the oxyacylation reaction of ethylene and propylene. Background Art

[0002] In 1968, Bayer first developed a method for producing vinyl acetate from gas-phase ethylene, acetic acid and oxygen. Due to its simple process flow, strong production capacity and good catalyst stability, many companies have developed and optimized it in the past 60 years. Now the Bayer process has become the mainstream process for producing vinyl acetate. The Bayer process uses a supported precious metal catalyst, the active components are Pd and Au, and the carrier is SiO2. Specifically, in a fixed bed tubular reactor, the reaction of a mixed gas containing ethylene, acetic acid, oxygen and nitrogen is carried out through a catalyst.

[0003] German patent DE1793447B2 discloses a method for producing vinyl acetate by reacting ethylene with oxygen and acetic acid in a liquid phase in the presence of palladium or salt, a redox system and an acetate ion forming agent, which can achieve a space-time yield of vinyl acetate of 795 g / (L*h).

[0004] German patent DE102007025362 discloses a method for preparing a shell catalyst for producing vinyl acetate monomer, wherein the catalyst carrier has a shell containing Pd and Au, and is characterized in that the noble metal catalyst is relatively evenly distributed in an area of ​​90% of the shell thickness.

[0005] Shanghai Petrochemical Research Institute CN102371182 discloses a preparation method using an organic chelating agent solution of palladium compounds and copper compounds to impregnate an alkaline carrier. The thickness of the Pd-Cu alloy layer in the obtained catalyst is 50 to 300 μm, which improves the thickness of the Pd-Cu alloy layer and solves the problems of low reaction activity and selectivity.

[0006] Patent CN102227259 disclosed by Clariant of Germany uses natural layered silicate, which is treated to obtain a carrier, and the shell catalyst prepared therefrom is used in the reaction of synthesizing vinyl acetate monomer.

[0007] The existing technology is difficult to solve the problems of low selectivity and short service life of supported catalysts in the oxyacylation reaction of gaseous olefins with acetic acid and oxygen, resulting in high production costs of vinyl acetate and allyl acetate. Summary of the invention

[0008] The purpose of the present invention is to provide a method for preparing a supported catalyst to improve the selectivity of the catalyst and extend the life of the catalyst. The catalyst obtained by the method of the present invention can be used in the gas phase oxidative acylation reaction of ethylene and propylene, and has high selectivity and service life.

[0009] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0010] A carrier molding method comprises the following steps: modifying natural bentonite through acid treatment, washing, drying and crushing, adding manganese oxide and copper oxide and a binder to press and mold, and obtaining the carrier after polishing and roasting.

[0011] The main component of natural bentonite is montmorillonite, which has a layered structure, and its main components are SiO2 and Al2O3. According to the different types of interlayer cations, it is divided into sodium-based bentonite and calcium-based bentonite. The present invention prefers natural calcium-based bentonite, wherein the SiO2 content is greater than 50%, preferably greater than 70%; the Al2O3 content is less than 20%, preferably less than 15%. The CaO content is 1% to 5%, preferably 1.5% to 3%; the cation exchange capacity (Cation Exchange Capacity, CEC) is 400 to 650 ml / kg, preferably 500 to 600 ml / kg, wherein the CEC value is measured according to the ammonium chloride-ammonium acetate method in the standard LYT1243-1999 "Determination of cation exchange capacity of forest soil".

[0012] The above-mentioned natural calcium-based bentonite is crushed, sieved, and soaked in an acid solution for impurity removal to obtain modified bentonite. The acid treatment process can remove impurity metals in natural bentonite, such as Mg, Na, K, Fe and Ti, and can also remove part of the aluminum oxide. The acid solution used is one of the strong acids in nitric acid, hydrochloric acid or sulfuric acid, and one of the weak acids in acetic acid and phosphoric acid. Preferably, the concentration of the acid solution is as follows: 98wt% sulfuric acid, 68-70wt% nitric acid, 35-37wt% hydrochloric acid, 99wt% acetic acid and 99wt% phosphoric acid. The mass fraction of strong acid in the mixed acid accounts for 50% to 90%, preferably 70% to 90%. The treatment temperature is 60-150℃, preferably 80-120℃; the treatment time is 4-24 hours, preferably 8-16 hours. Generally, a plate and frame filter press is used to separate the waste acid from the solid matter, and the filter cake is washed with deionized water. The end point of the washing is that the filtrate conductivity value is less than 50μs / μm. At this time, the element composition in the filter cake is measured. The SiO2 content in the treated modified bentonite is greater than 90%, preferably greater than 95%; the Al2O3 content is less than 10%, preferably less than 5%; the Ca content is 500-5000ppm, preferably 500-2000ppm; the Na content is less than 500ppm, preferably less than 100ppm; the Mg content is less than 500ppm, preferably less than 100ppm; the K content is 1000-5000ppm, preferably 1000-2000ppm; the Ti content is 1000-5000ppm, preferably 1000-2000ppm; the S content is less than 1000ppm, preferably less than 200ppm; the Cl content is less than 1000ppm, preferably less than 200ppm; and the contents of the remaining elements are all less than 500ppm, more preferably less than 100ppm.

[0013] The obtained filter cake is dried at a drying temperature of 60 to 120°C, preferably 80 to 110°C. The dried solid is crushed to a suitable size distribution, wherein the particle size distribution of the modified bentonite has a D50 of 1 to 50 μm, preferably 10 to 30 μm, and a D90 of less than 100 μm, preferably less than 60 μm; the bulk density of the powder is 0.5 to 0.8 g / ml, preferably 0.6 to 0.75 g / ml. The D50 value indicates that 50% of the powder particle size is below this value, and the D90 value indicates that 90% of the powder particle size is below this value. The bulk density of the powder is tested by a vibrator, and the average value is taken after three measurements using a 50 mL measuring cylinder.

[0014] As a preferred solution, the carrier forming process is as follows: a certain amount of modified bentonite is weighed, and manganese oxide and copper oxide powder are added, wherein the manganese oxide is 1-5% of the mass of the modified bentonite and the copper oxide is 1-3% of the mass of the powder after acid treatment. The particle size D50 of the manganese oxide powder is 1-50 μm, preferably 5-20 μm, and the particle size D50 of the copper oxide powder is 1-50 μm, preferably 5-15 μm.

[0015] Add organic and inorganic binders and knead them, then press them into shape. The inorganic binder is preferably one or more of silica sol, aluminum sol and 10-35% by mass of dilute nitric acid; the organic binder is preferably one or more of glycerol, calcium stearate, ethyl cellulose and hydroxypropyl methylcellulose. The mass fraction of the inorganic binder is 5-20% of the mass of the modified bentonite, preferably 5-10%, and the organic binder is 1-10% of the mass of the modified bentonite, preferably 1-5%. The shape of the molding is cylindrical, spherical, ellipsoidal, irregular particles, preferably spherical and ellipsoidal. After molding, its size is 1-8mm, preferably 3-6mm.

[0016] After forming, the organic binder needs to be burned off through a calcination process. The temperature at the highest point of calcination is 400-800°C, preferably 500-700°C; the time for maintaining the highest point temperature is 2-10 hours, preferably 2-8 hours.

[0017] The carrier was obtained after calcination. The pore structure of the carrier was determined by nitrogen physical adsorption and desorption method, and the specific surface area was 100-250m 2 / g, preferably 130-180m 2 / g; pore volume is 0.2-0.5ml / g, preferably 0.35-0.45ml / g; average pore diameter is 5-15nm, preferably 8-12nm. The carrier is characterized in that the water absorption rate is 40-80%, preferably 50-70%; the bulk density is 0.3-1g / ml, preferably 0.4-0.7g / ml. The interlayer spacing of the modified bentonite in the carrier is 1.2-2.0nm, preferably 1.4-1.8nm.

[0018] The method for determining the bulk density of the carrier is the same as the method for testing the bulk density of the powder. The method for determining the water absorption rate is as follows: place the carrier in an oven at 100-120°C for 4 hours, weigh 10g of the thoroughly dried carrier, add 50g of deionized water, let it stand for 2 hours, use paper to absorb the surface water, and measure the mass m when the adsorption is saturated. The water absorption rate = (m-10) / 10*100%. Repeat three times to measure the water absorption rate of the carrier.

[0019] The catalyst is prepared by loading the active component palladium and the auxiliary agent onto the above-mentioned carrier by the deposition precipitation method. The process of the deposition precipitation method is as follows: first, the active component palladium and the salt of gold / copper are prepared into a uniform solution, the volume of the solution is the volume of the carrier when it is saturated with water, the carrier and the solution are mixed evenly, and then put into an alkaline solution to precipitate the metal on the surface of the carrier, and the precursor is obtained after drying and reduction. Sodium acetate or potassium acetate solution is impregnated onto the surface of the precursor, and the catalyst is obtained after drying. The mass fraction of palladium is 0.1-2% of the mass of the dry-based carrier, preferably 0.25%-1%; the mass fraction of gold or copper is 0.1-2% of the mass of the dry-based carrier, preferably 0.15%-1%, (c) the mass fraction of potassium acetate or sodium acetate is 5%-20% of the mass of the dry-based carrier, preferably 5%-15%.

[0020] In the presence of the supported catalyst prepared as described above, acetic acid, oxygen, and gaseous olefins are used as raw materials to prepare vinyl acetate and allyl acetate. The specific reaction process is as follows: acetic acid, oxygen, and gaseous olefins are fed into a reactor filled with the catalyst of the present invention, the raw materials are calculated in a molar ratio of gaseous olefin: acetic acid: oxygen = 20-40%: 8%-12%: 4-8%, and the remaining components are nitrogen. The reaction conditions are a temperature of 140-180°C, a pressure of 0.4-0.9MPa, and a volume space velocity of 1000-3000h -1 .

[0021] The present invention has the following beneficial effects:

[0022] 1) The present invention obtains modified bentonite powder with suitable particle size distribution by acid treatment of natural calcium-based bentonite, and adds manganese oxide and copper oxide powder during the molding process to obtain a carrier with suitable interlayer spacing, which is conducive to the contact between the reactant and the active component and improves the diffusion effect of the heavy component.

[0023] 2) The supported catalyst prepared by the present invention has a suitable distribution of metal elements and a pore structure in the carrier, which can inhibit the agglomeration of precious metals and improve the selectivity of the main reaction, thereby providing a competitive catalyst for the oxyacylation process of ethylene and propylene. DETAILED DESCRIPTION

[0024] The present invention is further described below by means of specific examples. The examples described in the present invention are only used to illustrate the present invention and do not limit the scope of the present invention.

[0025] The calculation method and test method used in the embodiments or comparative examples are as follows:

[0026] 1. Use gas chromatography and Agilent GC 8890A chromatograph to analyze the content of each component in the reaction product, and calculate the activity and selectivity of the catalyst according to the following formula, taking allyl acetate as an example:

[0027]

[0028] 2. Determination of catalyst specific surface area and pore structure information

[0029] The pore structure of the catalyst was determined by N2 physical adsorption method, the specific surface area was obtained by BET method, and the pore volume was obtained by BJH desorption method. The testing instrument model was Micromeritics ASAP 2460.

[0030] 3. Determination of elemental composition

[0031] The elemental compositions of natural bentonite, modified bentonite, carrier and catalyst were determined by Epsilon 4 X-ray fluorescence spectrometer produced by PAN alytical.

[0032] 4. Determination of powder particle size distribution

[0033] Weigh 1 g of powder and add it to 50 mL of deionized water. Ultrasonicate for 15 minutes, stir it evenly, and then drop it into the test chamber of the laser particle size distribution analyzer. Repeat three times and take the average result of the measurement.

[0034] 5. Test of X-ray diffraction spectrum and calculation of relative crystallinity

[0035] The crystal phase of the sample was analyzed by using a Miniflex 600 X-ray diffractometer produced by Rigaku Corporation of Japan, using Cu target Kα radiation, with a tube voltage of 40 kV, a scanning range of 2θ=5-50°, and a scanning rate of 20° / min.

[0036] The method for calculating the relative crystallinity (RC) of the molecular sieve is as follows: taking the raw material mineral as the standard sample, by calculating the peak area of ​​the characteristic diffraction peak of the sample corresponding to the crystal plane at 2θ=26.6°, based on the peak area of ​​the raw material mineral, the crystallinity is defined as 100%, and the ratio of the peak area of ​​other samples at 2θ=26.6° to the peak area of ​​the raw material mineral is the relative crystallinity of the sample.

[0037] 6. Test method for interlayer spacing of bentonite

[0038] From the Bragg equation, we know that 2dsinθ=λ, and the interlayer spacing d is calculated based on the position of 2θ in the 5-10° range in the X-ray diffraction spectrum.

[0039] [Example 1]

[0040] Take 1kg of natural calcium-based bentonite, of which the SiO2 content is 75.1%, the Al2O3 content is 14.6%, the CaO content is 4.8%, and the exchangeable cation content value is 509ml / kg. Prepare 1L of sulfuric acid and acetic acid mixture, in which the mass fraction of sulfuric acid accounts for 80%, add natural calcium-based bentonite to the mixed acid, and treat it at 80℃ for 8 hours. After the acid treatment, wash with deionized water, the conductivity at the end of the washing is 25μs / μm, dry in a 120℃ oven, and then crush. The element composition of the modified bentonite includes 95.7% SiO2 mass fraction, 3.9% Al2O3 mass fraction, 512ppm Ca content, 95ppm Na content, 91ppm Mg content, 1065ppm K content, 1087ppm Ti content, 112ppm S content, and 84ppm Cl content. The particle size distribution D50 is 10.5μm, D90 is 48.6μm, and the bulk density of the powder is 0.75g / mL. 800g of the acid-treated precursor is weighed on a balance, and 18.4g of manganese oxide powder and 8.8g of copper oxide powder are added, wherein the D50 of manganese oxide powder is 17.5μm, and the D50 of copper oxide powder is 10.6μm. 15g of 10% nitric acid, 60g of 30% silica sol, 25g of calcium stearate, 8g of glycerol, and 8g of hydroxypropyl methylcellulose are weighed on a balance. The solid binder and the modified bentonite were mixed and then the mixture of the liquid binder was slowly added dropwise, stirring continuously during the addition process. The mixture was formed into a sphere using a molding device, and the diameter of the sphere was 6 mm. The obtained sphere was calcined at 500°C for 8 hours to prepare a carrier. The water absorption rate of the carrier was 68%, the bulk density was 0.42 g / ml, and the specific surface area was 178.5 m 2 / g, the pore volume is 0.44mL / g, the average pore diameter is 11.2nm, the relative crystallinity of the carrier is 96%, and the interlayer spacing is measured to be 1.8nm through the position of 2θ in the XRD diffraction spectrum.

[0041] Prepare 68 ml of an aqueous solution containing 0.417 g of palladium chloride and 0.402 g of cupric chloride dihydrate, stir well and evenly, and slowly and evenly contact with 100 g of the dried carrier to obtain intermediate 1; then add 500 mL of a 0.4 mol / L sodium hydroxide solution to obtain intermediate 2; reduce intermediate 2 at 200°C in a propylene atmosphere for 4 hours to obtain intermediate 3; prepare 68 mL of an aqueous solution containing 12.56 g of potassium acetate, and slowly and evenly contact with intermediate 3 to obtain intermediate 4; calcine intermediate 4 at 600°C for 8 hours to obtain a fresh catalyst.

[0042] The catalyst was heated to 140°C, the reaction pressure was 0.4 MPa, and the volume space velocity was 2500 h -1The raw material composition is ethylene: acetic acid: oxygen = 30%: 10%: 8%, and the remaining components are inert gases. After the reaction stabilizes, the catalyst activity is 838g / L / h, and the vinyl acetate selectivity is 98.1%. After running 1000 small tests, the catalyst activity is 815g / L / h, and the vinyl acetate selectivity is 97.8%.

[0043] [Example 2]

[0044] Take 1kg of natural calcium-based bentonite, of which the SiO2 content is 72.8%, the Al2O3 content is 12.4%, the CaO content is 3.5%, and the exchangeable cation content value is 546ml / kg. Prepare 1L of nitric acid and phosphoric acid mixture, in which the mass fraction of nitric acid accounts for 80%, add natural calcium-based bentonite to the mixed acid, and treat it at 100℃ for 12 hours. After the acid treatment, wash with deionized water, the conductivity at the end of the washing is 34μs / μm, dry in a 120℃ oven, and then crush. The element composition of the modified bentonite includes 97.6% SiO2 mass fraction, 2.1% Al2O3 mass fraction, 1892ppm Ca content, 80ppm Na content, 50ppm Mg content, 1684ppm K content, 1872ppm Ti content, 154ppm S content, and 59ppm Cl content. The particle size distribution D50 is 22.3μm, D90 is 54.8μm, and the bulk density of the powder is 0.68g / mL.

[0045] Weigh 800g of the acid-treated precursor on a balance, add 30.4g of manganese oxide powder and 18.4g of copper oxide powder, wherein the D50 of manganese oxide powder is 9.7μm and the D50 of copper oxide powder is 7.9μm. Weigh 10g of 35% nitric acid, 30g of 30% aluminum sol, 8g of glycerol, and 12g of ethyl cellulose on a balance. Mix the solid binder and modified bentonite, and then slowly add the mixture of liquid binder, stirring continuously during the addition process. Use a molding equipment to shape it into a sphere with a diameter of 6mm. The obtained sphere is calcined at 600°C for 4 hours to prepare a carrier. The water absorption of the carrier is 52%, the bulk density is 0.67g / ml, and the specific surface area is 134.6m 2 / g, the pore volume is 0.42ml / g, the average pore diameter is 9.6nm, the relative crystallinity of the carrier is 94%, and the interlayer spacing is measured to be 1.6nm through the position of 2θ in the XRD diffraction spectrum.

[0046] Prepare 62 mL of an aqueous solution containing 2.17 g of palladium nitrate and 0.92 g of gold tetrachloride trihydrate, stir well and evenly, and slowly and evenly contact with 100 g of the dried carrier to obtain intermediate 1; then add 500 ml of a 0.5 mol / L sodium hydroxide solution to obtain intermediate 2; reduce intermediate 2 at 200° C. in a hydrogen atmosphere for 4 h to obtain intermediate 3; prepare 62 ml of an aqueous solution containing 35.65 g of sodium acetate, and slowly and evenly contact with intermediate 3 to obtain intermediate 4; calcine intermediate 4 at 600° C. for 8 hours to obtain a fresh catalyst.

[0047] The catalyst was heated to 160°C, the reaction pressure was 0.6 MPa, and the volume space velocity was 2000 h -1 The raw material composition is propylene: acetic acid: oxygen = 40%: 12%: 6%, and the remaining components are inert gases. After the reaction stabilizes, the catalyst activity is 397g / L / h, and the allyl acetate selectivity is 94.6%. After running 5000 small tests, the catalyst activity is 345g / L / h, and the allyl acetate selectivity is 94.3%.

[0048] [Example 3]

[0049] Take 1kg of natural calcium-based bentonite, of which the SiO2 content is 80.3%, the Al2O3 content is 10.1%, the CaO content is 1.2%, and the exchangeable cation content value is 589mL / kg. Prepare 1L of hydrochloric acid and acetic acid mixture, of which hydrochloric acid accounts for 90%, add natural calcium-based bentonite to the mixed acid, and treat it at 120℃ for 16 hours. After the acid treatment, wash with deionized water, the conductivity at the end of the washing is 46μs / μm, dry in a 120℃ oven, and then crush. The element composition of the modified bentonite includes 96.3% SiO2 mass fraction, 3.3% Al2O3 mass fraction, 1163ppm Ca content, 40ppm Na content, 78ppm Mg content, 1971ppm K content, 1482ppm Ti content, 86ppm S content, and 148ppm Cl content. The particle size distribution D50 is 28.7μm, D90 is 58.4μm, and the bulk density of the powder is 0.62g / ml.

[0050] Weigh 800g of the acid-treated precursor on a balance, add 39.2g of manganese oxide powder and 24g of copper oxide powder, wherein the D50 of manganese oxide powder is 5.8μm and the D50 of copper oxide powder is 5.1μm. Weigh 25g of 25% nitric acid, 30g of 30% silica sol, and 8g of glycerol on a balance. Mix the solid binder and modified bentonite, and then slowly add the mixture of liquid binder, stirring continuously during the addition process. Use a molding equipment to shape it into a sphere with a diameter of 6mm. The obtained sphere is calcined at 700°C for 2 hours to prepare a carrier. The water absorption of the carrier is 63%, the bulk density is 0.58g / mL, and the specific surface area is 160.4m 2 / g, the pore volume is 0.36ml / g, the average pore diameter is 8.1nm, the relative crystallinity of the carrier is 98%, and the interlayer spacing is measured to be 1.4nm through the position of 2θ in the XRD diffraction spectrum.

[0051] Prepare 63 mL of an aqueous solution containing 0.835 g of palladium chloride and 3.150 g of copper acetate monohydrate, stir well and evenly, and slowly and evenly contact with 100 g of the dried carrier to obtain intermediate 1; then add 500 ml of a 0.35 mol / L sodium hydroxide solution to obtain intermediate 2; reduce intermediate 2 under 200°C ethylene atmosphere for 4 h to obtain intermediate 3; prepare 63 mL of an aqueous solution containing 37.69 g of potassium acetate, and slowly and evenly contact with intermediate 3 to obtain intermediate 4; calcine intermediate 4 at 600°C for 8 hours to obtain a fresh catalyst.

[0052] The catalyst was heated to 180°C, the reaction pressure was 0.9 MPa, and the volume space velocity was 2500 h -1 The raw material composition is propylene: acetic acid: oxygen = 20%: 8%: 4%, and the remaining components are inert gases. After the reaction stabilizes, the catalyst activity is 403g / L / h, and the allyl acetate selectivity is 95.2%. After running 5000 small tests, the catalyst activity is 379g / L / h, and the allyl acetate selectivity is 94.6%.

[0053] [Comparative Example 1]

[0054] Commercially available SiO2 is used as a carrier, 63 mL of an aqueous solution containing 0.835 g of palladium chloride and 3.150 g of copper acetate monohydrate is prepared, the solution is fully stirred, and the solution is slowly and evenly contacted with 100 g of the dried carrier to obtain intermediate 1; then 500 ml of a 0.35 mol / L sodium hydroxide solution is added to obtain intermediate 2; intermediate 2 is reduced at 200°C in an ethylene atmosphere for 4 h to obtain intermediate 3; 63 mL of an aqueous solution containing 37.69 g of potassium acetate is prepared, the solution is slowly and evenly contacted with intermediate 3 to obtain intermediate 4; intermediate 4 is calcined at 600°C for 8 hours to obtain a fresh catalyst.

[0055] The catalyst was heated to 180°C, the reaction pressure was 0.9 MPa, and the volume space velocity was 2500 h -1 The raw material composition is propylene: acetic acid: oxygen = 20%: 8%: 4%, and the remaining components are inert gases. After the reaction stabilizes, the catalyst activity is 258g / L / h, and the selectivity for allyl acetate is 92.6%. After running a small test for 100h, the catalyst activity is 237g / L / h, and the selectivity for allyl acetate is 92.3%.

Claims

1. A method for preparing a supported catalyst, characterized in that: The method comprises the following steps: modifying natural bentonite by acid treatment, washing, drying and crushing, adding manganese oxide and copper oxide and a binder to press into shape, polishing and roasting to obtain a carrier; and loading an active component, preferably palladium, as well as gold or copper and an auxiliary agent onto the carrier by a deposition precipitation method to prepare a catalyst.

2. The preparation method according to claim 1, characterized in that Natural bentonite is calcium-based bentonite, and its main components include SiO2 and Al2O3, wherein the SiO2 content is greater than 50%, preferably greater than 70%; the Al2O3 content is less than 20%, preferably less than 15%; wherein the CaO content is 1% to 5%, preferably 1.5% to 3%; and the cation exchange capacity value is 400 to 650 ml / kg, preferably 500 to 600 ml / kg.

3. The preparation method according to claim 1 or 2, characterized in that: The acid treatment process uses one of the strong acids among nitric acid, hydrochloric acid or sulfuric acid, and one of the weak acids among acetic acid and phosphoric acid, the mass fraction of the strong acid in the mixed acid accounts for 50% to 90%, preferably 70% to 90%; and / or, the acid treatment temperature is 60 to 150° C., preferably 80 to 120° C.; the treatment time is 4 to 24 hours, preferably 8 to 16 hours.

4. The preparation method according to any one of claims 1 to 3, characterized in that The SiO2 content in the modified bentonite after acid treatment is greater than 90%, preferably greater than 95%; the Al2O3 content is less than 10%, preferably less than 5%; the Ca content is 500-5000ppm, preferably 500-2000ppm; the Na content is less than 500ppm, preferably less than 100ppm; the Mg content is less than 500ppm, preferably less than 100ppm; the K content is 1000-5000ppm, preferably 1000-2000ppm; the Ti content is 1000-5000ppm, preferably 1000-2000ppm; the S content is less than 1000ppm, preferably less than 200ppm; the Cl content is less than 1000ppm, preferably less than 200ppm; the contents of other elements are all less than 500ppm, more preferably less than 100ppm.

5. The preparation method according to any one of claims 1 to 4, characterized in that The particle size distribution of the dried and crushed modified bentonite is D50 of 1 to 50 μm, preferably 10 to 30 μm, and D90 of less than 100 μm, preferably less than 60 μm; the bulk density of the powder is 0.5 to 0.8 g / mL, preferably 0.6 to 0.75 g / mL.

6. The preparation method according to any one of claims 1 to 5, characterized in that Based on the mass of the powder after acid treatment, manganese oxide is 1-5% of its mass, and copper oxide is 1-3% of its mass; preferably, the particle size D50 of the manganese oxide powder is 1-50 μm, preferably 5-20 μm, and the particle size D50 of the copper oxide powder is 1-50 μm, preferably 5-15 μm.

7. The preparation method according to any one of claims 1 to 6, characterized in that The binder used is a mixture of an inorganic binder and an organic binder, wherein the inorganic binder is preferably one or more of silica sol, aluminum sol and 10-35% by mass of dilute nitric acid; the organic binder is preferably one or more of glycerol, calcium stearate, ethyl cellulose and hydroxypropyl methylcellulose; preferably, based on the mass of the powder after acid treatment, the mass fraction of the inorganic binder is 5-20%, preferably 5-10%; the mass fraction of the organic binder is 1-10%, preferably 1-5%.

8. The preparation method according to any one of claims 1 to 7, characterized in that The temperature at the highest point of calcination is 400-800° C., preferably 500-700° C.; the time maintained at the highest point temperature is 2-10 hours, preferably 2-8 hours.

9. The preparation method according to any one of claims 1 to 8, characterized in that The obtained carrier has a water absorption rate of 40-80%, preferably 50-70%; a bulk density of 0.3-1 g / ml, preferably 0.4-0.7 g / ml; and a specific surface area of ​​100-250 m 2 / g, preferably 130-180m 2 / g; the pore volume is 0.2-0.5 ml / g, preferably 0.35-0.45 ml / g; the average pore diameter is 5-15 nm, preferably 8-12 nm.

10. The preparation method according to any one of claims 1 to 9, characterized in that: After forming, the interlayer distance of the modified montmorillonite in the carrier is 1.2 to 2.0 nm, preferably 1.4 to 1.8 nm.

11. The catalyst prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The invention comprises an active component of palladium, whose mass fraction is 0.1-2% of the mass of the dry-based carrier, preferably 0.25%-1%; gold or copper, whose mass fraction is 0.1-2% of the mass of the dry-based carrier, preferably 0.15%-1%; and an auxiliary agent of potassium acetate or sodium acetate, whose mass fraction is 5%-20% of the mass of the dry-based carrier, preferably 5%-15%.

12. Use of the catalyst prepared by the preparation method according to any one of claims 1 to 10 or the catalyst according to claim 11 in the gas-phase oxidative acylation reaction of ethylene and propylene; preferably, catalyzing the gas-phase reaction of ethylene, propylene with acetic acid and oxygen to produce vinyl acetate and allyl acetate, the reaction temperature is 140-180° C., the reaction pressure is 0.4-0.9 MPa, and the feed molar ratio of olefin: acetic acid: oxygen is 20-40%: 8%-12%: 4-8%.

Citation Information

Patent Citations

  • doped Pd / Au shell catalyst, process for its production and its use

    DE102007025362A1

  • PROCESS FOR PRODUCTION OF VINYL ACETATE

    DE1793447B2

Cited By

  • Preparation method and application of high-strength water-resistant multifunctional efficient granular activated clay preparation

    CN121571120A